Extent of disability among paediatric Japanese encephalitis survivors and predictors of poor outcome: a retrospective cohort study in North India. Issue 10 (31st October 2022) - Srivastava, Neha; Deval, Hirawati; Mittal, Mahima; Deoshatwar, Avinash; Bondre, Vijay P; Kant, Rajni; Yadav, Rajaram
Abstract : Objective: To determine the Japanese encephalitis (JE)-associated long-term functional and neurological outcomes, the extent of reduced social participation and predictors of poor outcomes among paediatric JE survivors. Design: A retrospective cohort study. Setting: Laboratory-confirmed JE-positive paediatric cases (<16 years of age) hospitalised at the paediatric ward of Baba Raghav Das Medical College, Gorakhpur, India, between 1 January 2017 and 31 December 2017, were followed up after 6–12 months of hospital discharge. Participants: 126 patients were included in the study; median age was 7.5 years (range: 1.5–15 years), and 74 (58.73%) were male. Outcome measures: Functional outcome defined by Liverpool Outcome Score (LOS) dichotomised into poor (LOS=1–2) and good (LOS=3–5) outcome groups compared for demographic, clinical and biochemical parameters for prognostic factors of poor outcomes. Social participation of patients scaled on Child and Adolescent Scale of Participation score 2–5. Results: About 94 of 126 (74.6%) children developed neurological sequelae at different levels of severity. Age-expected social participation was compromised in 90 out of 118 children. In multivariate logistic regression analysis, a combination of parameters, JE unvaccinated status (OR: 61.03, 95% CI (14.10 to 264); p<0.001), low Glasgow Coma Score (GCS) at admission (≤8) (OR: 8.6, 95% CI (1.3 to 57.1); p=0.026), malnutrition (OR: 13.56, 95% CI (2.77 to 66.46); p=0.001) and requirement of endotracheal intubation (OR: 5.43, 95% CI (1.20 to 24.44); p=0.027) statistically significantly predicted the poor outcome with 77.8% sensitivity and 94.6% specificity. The goodness-of-fit test showed that the model fit well (Hosmer-Lemeshow goodness-of-fit test) ( χ 2 =3.13, p=0.988), and area under the receiver operating characteristic curve was 0.950. Conclusion: This study estimates the burden of JE-presenting post-discharge deaths (15.4%) and disability (63.08%). Those who did not receive JE vaccine, were suffering from malnutrition, had GCS ≤8 at admission and required endotracheal intubation had poorer outcomes.